Electron irradiation of nuclear graphite studied by transmission electron microscopy and electron energy loss spectroscopy. (March 2015) - Mironov, B.E.; Freeman, H.M.; Brown, A.P.; Hage, F.S.; Scott, A.J.; Westwood, A.V.K.; Da Costa, J.-P.; Weisbecker, P.; Brydson, R.M.D.
Abstract: Structural and chemical bonding changes in nuclear graphite have been investigated during in-situ electron irradiation in a transmission electron microscope (TEM); electron beam irradiation has been employed as a surrogate for neutron irradiation of nuclear grade graphite in nuclear reactors. This paper aims to set out a methodology for analysing the microstructure of electron-irradiated graphite which can then be extended to the analysis of neutron-irradiated graphites. The damage produced by exposure to 200 keV electrons was examined up to a total dose of approximately 0.5 dpa (equivalent to an electron fluence of 5.6 × 10 21  electrons cm −2 ). During electron exposure, high resolution TEM images and electron energy loss spectra (EELS) were acquired periodically in order to record changes in structural (dis)order and chemical bonding, by quantitatively analysing the variation in phase contrast images and EEL spectra.